KONTRIBUSI INTERIOR KELAS DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR PPKN - Purwanti, Eko; Kristiyani, Ika (Program Studi Pendidikan Guru Sekolah Dasar Universi, 2019)
Regular class design make students uncomfortable and uninterested in learning. The purpose of this study was to examine the contribution of the interior of classroom and learning motivation on learning outcomes PPKn. This study used correlational study. Technique sampling using simple random sampling. The technique of collecting data using questionnaires, documentation, observation, and interviews. Test instrument through validity and reliability test. The data analysis technique used is the prerequisite test data analysis, descriptive statistical analysis, correlation analysis, and regression analysis. The results showed that there was a positive and significant correlation between class interior and learning motivation towards learning outcomes PPKN with a very strong category and contributes quite high which means that the interior of classroom and learning motivation plays a role in improving student learning outcomes, especially in PPKn lesson. The final conclusion is that the interior of classroom and learning motivation contribute to the learning outcomes PPKn Force Elementary School third grade Draupadi Gunungpati District of Semarang